-2n+5.9n+5.77=2.8n-15.9

Simple and best practice solution for -2n+5.9n+5.77=2.8n-15.9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2n+5.9n+5.77=2.8n-15.9 equation:


Simplifying
-2n + 5.9n + 5.77 = 2.8n + -15.9

Reorder the terms:
5.77 + -2n + 5.9n = 2.8n + -15.9

Combine like terms: -2n + 5.9n = 3.9n
5.77 + 3.9n = 2.8n + -15.9

Reorder the terms:
5.77 + 3.9n = -15.9 + 2.8n

Solving
5.77 + 3.9n = -15.9 + 2.8n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2.8n' to each side of the equation.
5.77 + 3.9n + -2.8n = -15.9 + 2.8n + -2.8n

Combine like terms: 3.9n + -2.8n = 1.1n
5.77 + 1.1n = -15.9 + 2.8n + -2.8n

Combine like terms: 2.8n + -2.8n = 0.0
5.77 + 1.1n = -15.9 + 0.0
5.77 + 1.1n = -15.9

Add '-5.77' to each side of the equation.
5.77 + -5.77 + 1.1n = -15.9 + -5.77

Combine like terms: 5.77 + -5.77 = 0.00
0.00 + 1.1n = -15.9 + -5.77
1.1n = -15.9 + -5.77

Combine like terms: -15.9 + -5.77 = -21.67
1.1n = -21.67

Divide each side by '1.1'.
n = -19.7

Simplifying
n = -19.7

See similar equations:

| 7y-4y^2+15=0 | | (4+x)*3=x+18 | | 4x+11=-25 | | 110=-5(2p-8) | | -1(2n+3)=2(-4n+-3) | | 4x-2x-2x=2x | | 0.2x+6.1=5.6 | | 7m-2=53 | | 4(-4+4x)=96 | | 0.6t-15.48=-9.04+t | | P^2-12=-p | | -3+5(3x+6)=102 | | -29-1=6(1+3k) | | X+x(.0875)+x(.20)=125 | | f(x)=300-2x | | 3x-23=4x+6 | | -5(n+2)=8-4n | | j=14+2j | | 10d+29.99=60 | | 9=5+3.5n | | 14=8+5x+1 | | 3a+5=29+7 | | (12)x=16(x-2) | | 4+X*3=X+18 | | 13w+1=20+14w | | -3p+6=4p-24 | | 4+5=-13 | | X^2+7x+7=-5 | | -4+-3z=6+-3z | | 2z=-12-4z | | C=8(pi) | | 3y-4=20+6y |

Equations solver categories